Vitamin E Delivery Systems Increase Resistance to Oxidative Stress in Red Deer Sperm Cells: Hydrogel and Nanoemulsion Carriers - Alejandro Jurado-Campos; Pedro Javier Soria-Meneses; Francisca Sánchez-Rubio; Enrique Niza; Iván Bravo; Carlos Alonso-Moreno; María Arenas-Moreira; Olga García-Álvarez; Ana Josefa Soler; José Julián Garde; María del Rocío Fernández-Santos (MDPI AG, 2021)
Oxidative stress has become a major concern in the field of spermatology, and one of the possible solutions to this acute problem would be the use of antioxidant protection; however, more studies are required in this field, as highly contradictory results regarding the addition of antioxidants have been obtained. Vitamin E is a powerful biological antioxidant, but its low stability and high hydrophobicity limit its application in spermatology, making the use of organic solvents necessary, which renders spermatozoa practically motionless. Keeping this in mind, we propose the use of hydrogels (HVEs) and nanoemulsions (NVEs), alone or in combination, as carriers for the controlled release of vitamin E, thus, improving its solubility and stability and preventing oxidative stress in sperm cells. Cryopreserved sperm from six stags was thawed and extended to 30 × 106 sperm/mL in Bovine Gamete Medium (BGM). Once aliquoted, the samples were incubated as follows: control, free vitamin E (1 mM), NVEs (9 mM), HVEs (1 mM), and the combination of HVEs and NVEs (H + N), with or without induced oxidative stress (100 µM Fe2+/ascorbate). The different treatments were analyzed after 0, 2, 5, and 24 h of incubation at 37 °C. Motility (CASA®), viability (YO-PRO-1/IP), mitochondrial membrane potential (Mitotracker Deep Red 633), lipid peroxidation (C11 BODIPY 581/591), intracellular reactive oxygen species production (CM-H2DCFDA), and DNA status (SCSA®) were assessed. Our results show that the deleterious effects of exogenous oxidative stress were prevented by the vitamin E-loaded carriers proposed, while the kinematic sperm parameters (p ˂ 0.05) and sperm viability were always preserved. Moreover, the vitamin E formulations maintained and preserved mitochondrial activity, prevented sperm lipid peroxidation, and decreased reactive oxygen species (ROS) production (p ˂ 0.05) under oxidative stress conditions. Vitamin E formulations were significantly different as regards the free vitamin E samples (p < 0.001), whose sperm kinematic parameters drastically decreased. This is the first time that vitamin E has been formulated as hydrogels. This new formulation could be highly relevant for sperm physiology preservation, signifying an excellent approach against sperm oxidative damage.